HUBUNGAN DUA ARAH (SIMULTANEOUS) ANTARA PERGANTIAN AKUNTAN DAN PENDAPAT AUDIT: - FAHRUDDIN LUBIS (Jurnal Bisnis dan Akuntansi, 2000)
Previous studies examining the relation between the audit opinion andauditor switching assume a one way causation, with the issuance of aqualified opinion triggering a switch. However, analytical studies dealingwith auditor independence issues (e.g. Magee and tseng, 1990; Dye,1991; Teoh, 1992) suggest an opposite causation, in which the auditor isless likely to qualify the opinion for a client who may switch auditors. Some evidence of an opposite causation is provided by Krishnan (1994) , who finds that auditors treat switchers more conservatively in issuing the audit opinion. The causation between switching and the audit opinion is clearly important for policy decisions regarding both opinion shopping and auditor independence. In this paper, we test the two-way policy decisions regarding both opinon shopping and auditor independence. Our simultaneity-adjusted estimates comfirm previous findings of a positive effect of a qualified opinion in switching (Chow and rice, 1982; Craswell, 1988; Citron and Taffler, 1992). However, we find in addition that auditors are more likely to issue qualified opinions to switchers. This finding does not snpport the analytical studies cited earlier.